Pengaruh Product Quality, Brand Image, Dan Brand Trust Terhadap Keputusan Pembelian Iphone (Studi Kasus Mahasiswa Universitas Islam Malang) - Yuzky Maulana Irbad; Budi Wahono; Sulton Sholehuddin (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine "the effect of shopping Product Quality, Brand Image, and Brand Trust on Iphone Purchase Decisions" (on Iphone users at the Islamic University of Malang)". The type of research used in this research is quantitative research. The data processed in this study is the result of distributing questionnaires to students who have used the iPhone at least once, totaling 99 respondents. The sampling method is purposive sampling. The analysis technique used in this study is multiple linear regression. The results showed that the results of the t (partial) test on Product Quality had an effect on Purchasing Decisions indicated by a t value of 4.278, Brand Image had no effect on Purchase Decisions indicated by a t value of 0.535, and Brand Trust had no effect on Purchase Decisions indicated by a t value of 0.332. This means that Product Quality affects purchasing decisions while Brand Image and Brand Trust do not affect Purchase Decisions on Iphone at UNIVERSITAS ISLAM MALANG. Based on the calculation of the coefficient of determination, it shows that the Adjusted R Square is 20.4% and the remaining 79.6% can be explained by other variables that are not in this study Keywords: Product Quality, Brand Image, Brand Trust and Purchase Decision